SASAKAWA TECHNOLOGY A PANACEA TO MAIZE YIELD IMPROVEMENT AND MEETING THE VAGARIES OF CLIMATE CHALLENGE IN MUBI - Toungos, Mohammed D. (International Journal of Research -GRANTHAALAYAH, 2018)
This study determines the efficacy of Sasakawa technology to maize yield improvement and meeting the demand of the populace in terms of food crop production at the time of unpredictable weather conditions in Mubi. The field trials were conducted during the 2017 cropping season at the teaching and research farm of the Faculty of Agriculture, Adamawa state University Mubi to evaluate the effect of Sasakawa Technology as a panacea to maize yield improvement and meeting the vagaries of climate change in Mubi. Mubi, located in the Northern Guinea Savannah of Nigeria. Mubi is situated between latitude 100 10’’ and 100 30’’ North of the Equator and between longitude 130 10 and 130 30’’ E of the Greenwich meridian and at an altitude of 696 m above mean sea level (MSL). Extra early white (EEW) variety of maize was obtained from Farm office of the University, were sown at three different sowing dates 19th July, 29th July and 8th August, 2018. There was a large yield difference between the Sasakawa Technology of maize production and local farmers’ output in Mubi, despite the limited opportunities to sustainability and increase in the productivity of the crop in order to adapt to vagaries of climate change. Yields recorded during the three sowing dates were 2,967kg/ha, 2,930kg/ha and 2,921kg/ha while on the neighboring farmer’s field was 1,897kg/ha. It indicated that, the Sasakawa technology used in terms of spacing of 25cm x 25cm between plants and 75cm x75cm between rows, single seed per stand and appropriate fertilizer application increased maize yield more than the neighboring farmers fields. The Sasakawa technology recorded mostly two cobs per stand, longer cobs mean lengths with maximum grain filled and the grains were significantly bigger when compared to the farmer’s fields. Even though some critics argue that, Sasakawa Global 2000 technology deals with high-external-input technologies (HEIT) which are too costly to some farmers, but the out – put out weights the input in terms of yields, economic returns and also sustained the vagaries of climatic effects due to timely sowing and maintenance of the Sasakawa technology techniques. To boost maize production in Mubi and at this time of unpredictable climate and its effects, the Sasakawa technology is recommended to be adopted by the farmers.